Morphometric, Meristic, and growth patterns of Channa micropeltes Cuvier, 1831 from the Lubuk Siam Oxbow Lake, Kampar Regency, Riau Province - Handayani, Fitri; Efizon, Deni; Eddiwan, Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Channa micropeltes or toman fishis a freshwater fish that live in the Lubuk Siam Lake and it has high economical value. Information on the biological aspects of these fish wasrare.A research aims to understand morphometric and meristic of the fish has been conducted from January-March 2018. There were 62 fishes (145-580 mm TL and 107-2.200 g BW) captured. Twenty six morphometrical characteristics measure and 11 meristical characteristics counted. Male and female fish can be distinguished by the head and body shape. The head of the male is slightly pointed, the body is blackish and slimbody shape. Female has blunt head, bluish black and abdomen rounded. The meristical characteristics of the fish were as follow: D. 41-48, P. 12-17, V.6, A. 25-27, C.13-15. The number of scale in thecheek was 32-40,pre-dorsal fin was 30-33, in the lateral line was 100-120,around the body was 44-60, above and below the lateral line was 48-95. The length-weight relationship shown that the growth pattern of the fish in the Lubuk Siam Lake is positive allometric, b=3.105.Keywords: Channamicropeltes, Lubuk Siam Lake, Relative Growth